2015
DOI: 10.4161/15592294.2014.988035
|View full text |Cite
|
Sign up to set email alerts
|

ARHGEF3 controls HDACi-induced differentiation via RhoA-dependent pathways in acute myeloid leukemias

Abstract: Altered expression and activity of histone deacetylases (HDACs) have been correlated with tumorigenesis. Inhibitors of HDACs (HDACi) induce acetylation of histone and non-histone proteins affecting gene expression, cell cycle progression, cell migration, terminal differentiation and cell death. Here, we analyzed the regulation of ARHGEF3, a RhoA-specific guanine nucleotide exchange factor, by the HDACi MS275 (entinostat). MS275 is a well-known benzamide-based HDACi, which induces differentiation of the monobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 61 publications
2
19
0
Order By: Relevance
“…An alternative possibility is the regulation of ARHGEF3 activity by subcellular localization. A recent study has found that ARHGEF3 is normally enriched in the nucleus and it translocates into the cytoplasm upon inhibition of histone deacetylases, leading to activation of RhoA and actin cytoskeletal reorganization (D'Amato et al, 2015). Therefore, the RhoGEF activity of ARHGEF3 may be very low under normal conditions due to its nuclear sequestration, and it is switched on when specific conditions induce ARHGEF3 export from the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative possibility is the regulation of ARHGEF3 activity by subcellular localization. A recent study has found that ARHGEF3 is normally enriched in the nucleus and it translocates into the cytoplasm upon inhibition of histone deacetylases, leading to activation of RhoA and actin cytoskeletal reorganization (D'Amato et al, 2015). Therefore, the RhoGEF activity of ARHGEF3 may be very low under normal conditions due to its nuclear sequestration, and it is switched on when specific conditions induce ARHGEF3 export from the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…A related Rho-GEF, ARHGEF3, is also somewhat differentially spliced between Treg and Th2 cells in that a proximal alternative first exon is favored in Tregs versus Th2 cells, thus altering the first 32-38 amino acids of the encoded protein. While functional differences have not been identified between the isoforms with distinct N-termini, ARHGEF3 has been linked to activation of RhoA in myeloid development (D'Amato et al, 2015).…”
Section: Analysis Of Local Splicing Variations Reveals Treg-biased Ismentioning
confidence: 99%
“…DVL interacts with Figure 3) (16). While several GEFs are involved, and it has been reported that Daam1 interaction may be non-essential, it is clear that both RhoA and Rac1 are activated by Wnt ligand/ROR-1/2/DVL signaling (17)(18)(19). RhoA can be initiated separately from Rac1, and vice versa; while in some cell types, it has been observed that non-canonical signaling can stimulate Rac1, but inhibit RhoA (20)(21)(22).…”
Section: The Wnt Cascadementioning
confidence: 99%
“…RhoA activates the Rho-associated kinase (ROCK), which induces actin filament assembly and cytoskeletal changes (16,19). Further, RhoA affects cell survival mechanisms through JNK signaling (18). Rac1 signals through MEK/ERK pathways and JNK/NF-κb pathways, resulting in a net proliferative/pro-survival stimulus (23)(24)(25).…”
Section: The Wnt Cascadementioning
confidence: 99%